Undifferentiated Altered Mental Status: A Late Presentation of Toxic Acetaminophen Ingestion. (28th June 2012) - Robey, Thomas E.; Melnick, Edward R.
Abstract : Altered mental status is a common undifferentiated presentation in the emergency department. We describe a case of acetaminophen-induced acute liver failure that was diagnosed and treated prior to obtaining definitive historical or laboratory information about the etiology. The physical exam finding of scleral icterus in this case was a key element to rapid identification and treatment of this life-threatening condition. A discussion of appropriate N-acetylcysteine treatment for acute liver failure and acetaminophen intoxication is included.